2017
DOI: 10.1038/s41370-017-0010-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of blood volatile organic compound levels in Gulf coast residents

Abstract: To address concerns among Gulf Coast residents about ongoing exposures to volatile organic compounds, including benzene, toluene, ethylbenzene, o-xylene, and m-/p- xylene (BTEX), we characterized current blood levels and identified predictors of BTEX among Gulf state residents.We collected questionnaire data on recent exposures and measured blood BTEX levels in a convenience sample of 718 Gulf residents. Because BTEX is rapidly cleared from the body, blood levels represent recent exposures in the past 24 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…To address community concerns about exposure to potentially harmful oil spill-related chemicals among Gulf coast residents, we measured blood volatile organic compound (VOC) levels in a subset of Gulf Long-Term Follow-up Study (GuLF STUDY) participants 2–3 years after the Deepwater Horizon (DWH) oil spill. We previously reported that blood levels of specific oil-related VOCs such as benzene, toluene, ethylbenzene and xylenes were similar to those found in the National Health and Nutrition Examination Survey (NHANES) (1). Among the VOCs included in the CDC-based test panel, only styrene was substantially elevated.…”
Section: Introductionsupporting
confidence: 52%
“…To address community concerns about exposure to potentially harmful oil spill-related chemicals among Gulf coast residents, we measured blood volatile organic compound (VOC) levels in a subset of Gulf Long-Term Follow-up Study (GuLF STUDY) participants 2–3 years after the Deepwater Horizon (DWH) oil spill. We previously reported that blood levels of specific oil-related VOCs such as benzene, toluene, ethylbenzene and xylenes were similar to those found in the National Health and Nutrition Examination Survey (NHANES) (1). Among the VOCs included in the CDC-based test panel, only styrene was substantially elevated.…”
Section: Introductionsupporting
confidence: 52%
“…The 2,5-dimethylfuran acted as a smoking biomarker with good sensitivity and specificity. The cutoff point for differentiating between current daily smokers and less than daily smokers (< 1 CPD), which includes nonsmokers, was set at a blood 2,5-dimethylfuran concentration of 0.014 ng/mL [ 22 , 23 ]. We used this criteria to distinguish between daily smokers an non-daily smokers.…”
Section: Methodsmentioning
confidence: 99%
“…Ultimately, 11,193 home visits were completed between May 2011 and May 2013. A subset of home visit participants (n=1,055) enrolled in a Chemical Biomonitoring Study (CBS) between May 2012 and July 2013 (Werder et al. 2017).…”
Section: Methodsmentioning
confidence: 99%